Vancomycin Resistance in ICU setting- A Rising Menace - Umesh Patel; D Sharad Gedam (International Journal of Medical Research and Review, 2015)
Vancomycin-resistant organisms are significant nosocomial pathogens worldwide. Vancomycin resistant is a growing problem in the ICU setting. Treatment is difficult because of limited options (antibiotics) available.